Assessment of Performance of Commercial Banks in India - Sharma, Vijay Kumar; Kumar, Anuj (Indian Journal of Finance, 2013)
Commercial banks occupy a crucial role in the development efforts as well as act as a catalyst for economic growth. Banking reforms have brought sea changes in the banking space and public sector banks are no exception to this. The major concern in the Indian financial sector has been the profitability of the commercial banking industry. The opening up of the banking sector for private players has put pressure on better performance of public sector banks. The private and foreign banks with advanced technology and management skills have put pressure on the profitability of public sector banks. Hence, these public sector banks need to be equipped enough to counter the pressures, otherwise, repercussions are likely to be great. With this background, the paper investigates the impact of banking reforms on the performance of public, private, and foreign banks. The performance of a bank can be measured by a number of indicators. Profitability is the most important indicator which assumes a greater importance in the ever-changing scenario of financial sector reforms. The viability of banks depends largely on the adequacy of profits and profitability. The study has analyzed the impact of banking sector reforms on the performance of all bank groups in India in the pre and post reform period. The undertaken regressors showed a significant impact on total income in the post-reform period for all bank groups.